2019
DOI: 10.11648/j.am.20190802.13
|View full text |Cite
|
Sign up to set email alerts
|

The First Principles Study on Two Alloys of Cr2ZnAl and Cr2AgAl

Abstract: The Heusler alloy is with a ordered structure, in which the atoms are in specific location, and the alloy usually shows special character. The Co Mn Ni based Heusler alloys are all studied in many literature, but there is little study of the Cr based Heusler alloys. In order to find new Heusler alloys, Cr2AgAl and Cr2ZnAl are studied by first principles. Using the CALYPSO software, the crystal structure of Cr2AgAl is found to be F-43m, the lattice parameter is a=6.1100 Å, it is a Heusler alloy, and the density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…For intermetallic compounds, the crystal structure plays a crucial role in determining their physicochemical properties, which fundamentally affects the performance of alloy materials. In addition to chemical composition and temperature, pressure is a powerful tool in altering the packed configuration of atoms and interatomic distances, which can result in the appearance of unprecedented structural prototypes that may improve the performance of alloy or host compelling phenomena unavailable at ambient conditions [13][14][15][16][17]. An experimental study has found that a reserved high-pressure hexagonal close-packed phase of CoCrFeMnNi high-entropy alloy possesses superior hardness [18].…”
Section: Introductionmentioning
confidence: 99%
“…For intermetallic compounds, the crystal structure plays a crucial role in determining their physicochemical properties, which fundamentally affects the performance of alloy materials. In addition to chemical composition and temperature, pressure is a powerful tool in altering the packed configuration of atoms and interatomic distances, which can result in the appearance of unprecedented structural prototypes that may improve the performance of alloy or host compelling phenomena unavailable at ambient conditions [13][14][15][16][17]. An experimental study has found that a reserved high-pressure hexagonal close-packed phase of CoCrFeMnNi high-entropy alloy possesses superior hardness [18].…”
Section: Introductionmentioning
confidence: 99%